2020
DOI: 10.3390/nu12020405
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of the Effect of Replacing Sugar-Sweetened Soda by Reduced Fat Milk on Cardiometabolic Health in Male Adolescent Soda Drinkers

Abstract: Soda consumption in adolescents has been linked to poorer metabolic outcomes. We tested whether replacing soda with reduced fat milk would improve features of atherogenic dyslipidemia and other cardiometabolic risk factors. Thirty overweight and obese adolescent boys who were habitual consumers of sugar-sweetened beverages were randomly assigned to consume 24 oz/day of sugar-sweetened soda or an energy equivalent of reduced fat (2%) milk for 3 weeks with crossover to the alternate beverage after a ≥ 2 weeks wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“…We retrieved 4616 reports from databases and manual searches, 4433 of which were excluded based on the title or abstract. Of the 174 reports reviewed in full text, 51 reports of controlled feeding trials (75 trial comparisons, n = 2059) met the eligibility criteria [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. These trials included ten different food sources of fructos...…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 4616 reports from databases and manual searches, 4433 of which were excluded based on the title or abstract. Of the 174 reports reviewed in full text, 51 reports of controlled feeding trials (75 trial comparisons, n = 2059) met the eligibility criteria [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. These trials included ten different food sources of fructos...…”
Section: Resultsmentioning
confidence: 99%
“…In our work, high SSB intake was associated with increased systolic blood pressure and odds of hypertension; numerous trials also evaluated the effects of reduced SSB intake on blood pressure; in the study by Chen L et al reduction in SSB intake of 1 serving/day over 18 months was associated with a 1.8 and 1.1 mmHg reduction in SBP and DBP, respectively [43]. Chiu S et al also reported reduced systolic blood pressure after replacing sugar sweetened sodas with milk in young male adolescents [44]. Accumulating evidence has linked SSB consumption during childhood to unhealthy weight gain which itself associated with risk of health outcomes such as type 2 diabetes, metabolic syndrome, cardiovascular diseases and other obesity-related disorders in later life [45].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in young adults an increase in triglycerides and VLDL is associated with both acute and chronic fructose consumption ( 28 , 116 , 117 ), even at relatively low doses ( 118 ). Regarding the hypothesis of an association between consumption of SSBs and triglycerides in pediatric age, data are conflicting: some studies show an increase in triglyceridemia in children and adolescents with higher consumption of SSBs ( 113 , 115 , 118 ), whereas others studies do not show any significant differences ( 119 , 120 ).…”
Section: Fructose and Cardiometabolic Risk Factors In Pediatric Age: ...mentioning
confidence: 98%
“…The study included a cross-over phase between the two groups after a washout period. The SBP z-score and uricemia were significantly lower when milk was taken instead of SSBs ( 120 ). Only one study evaluated the consumption of sugars taken via solid foods (sugary snacks) and confirmed that the subjects with the highest level of consumption had an increased risk of being hypertensive.…”
Section: Fructose and Cardiometabolic Risk Factors In Pediatric Age: ...mentioning
confidence: 99%